Management, marketing and promotion of library services based on statistics, analyses and evaluation (Saur, 2006)
This book contains their presentations in the form of full length articles that strengthen the awareness of the potential of tools for management and strategic planning. The author are managers from different types of libraries, researchers and educators from five continents shared their experiences with research methods, data collection, evaluation, performance measurement, best practice strategies and policies. In order to cope with this phenomenon and to master the situation forms one of the biggest challenges facing libraries.